Completeness of Immunization in Infants Aged 0-9 Months: The Role of Mother's Knowledge and Belief: Kelengkapan Imunisasi pada Bayi Usia 0-9 Bulan: Peran Pengetahuan dan Kepercayaan Ibu - Irnawati, Irnawati; Kadek Sukmawati, Niluh (Poltekkes Kemenkes Palu, 2023)
Introduction: Over 1.4 million children have died from Immunization-Preventable Diseases (PD3I). The lack of socialization provided by health workers has an impact on the lack of understanding, admonition, and understanding of mothers when participating in immunization programs. Purpose: to determine the relationship between the knowledge and confidence of mothers on the completeness of immunization in infants aged 0-9 months. Method: using a cross-sectional research design, with a population of 216 infants, sampling using purposive sampling techniques totaling 54 respondents with inclusion criteria: infants aged 0-9 months and residing in the study area, while the exclusion criteria were babies who were sick during the study. The research was conducted in Kombo. Using questionnaires and using chi-square tests of vaccine availability. Results: there were 83.3% of respondents who had good knowledge and had complete immunization 75.9% and there were 16.6% who had less knowledge, had complete immunization of 9.1% with a value of ρ=0.006. Conclusion: there is a relationship between knowledge and maternal confidence in the completeness of immunization in infants aged 0 – 9 months. Parents should pay attention to their children's basic immunizations and public health guarantees the availability of vaccines